2016
DOI: 10.4103/0974-1208.197687
|View full text |Cite
|
Sign up to set email alerts
|

Female sexual dysfunction in patients with endometriosis: Indian scenario

Abstract: BACKGROUND:Female sexual dysfunction (FSD) in Indian women is often overlooked due to cultural beliefs and considered as social taboos. Sexuality is an important and integral part of life. There are many causes of sexual dysfunction, but the prevalence of FSD in endometriotic patients is still underdiagnosed.MATERIALS AND METHODS:Study design - Cross-sectional observational study conducted at tertiary care center, from June 2015 to March 2016. Sample size - Fifty-one patients in reproductive age group (18–47 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
6
1
1
Order By: Relevance
“…The finding of the current study revealed that the mean age of the study and control groups was 32.29 ± 2.58 (range: 27 to 41 years) and 31.54 ± 2.91 years (range: 26 to 45 years) respectively. This was nearly congruent with Rasheed et al (2010) who found no statistically significant difference between the two groups as regards the mean Mishra et al (2016) reported that the mean age of women was 28.51 ± 5.15 years. Also El-Maraghy et al (2017) reported that the mean age of the women with endometriosis was 37.3 years (range: 24 to 45 years).…”
Section: Discussionsupporting
confidence: 89%
“…The finding of the current study revealed that the mean age of the study and control groups was 32.29 ± 2.58 (range: 27 to 41 years) and 31.54 ± 2.91 years (range: 26 to 45 years) respectively. This was nearly congruent with Rasheed et al (2010) who found no statistically significant difference between the two groups as regards the mean Mishra et al (2016) reported that the mean age of women was 28.51 ± 5.15 years. Also El-Maraghy et al (2017) reported that the mean age of the women with endometriosis was 37.3 years (range: 24 to 45 years).…”
Section: Discussionsupporting
confidence: 89%
“…Mishra et al 28 reported an FSD rate of 47.06%, and a rise in sexual dysfunction with increasing stages of endometriosis. The rate of FSD increased from 33.33% in patients with minimal endometriosis to 100% in those with severe endometriosis 28 . The difference in FSD rates between the latter study and ours might be explained by the fact that the majority of patients in the present study had severe endometriosis.…”
Section: Discussionmentioning
confidence: 98%
“…These data are supported by two other studies, in which 70%-75% of women with endometriosis had FSD. 26,27 Mishra et al 28 reported an FSD rate of 47.06%, and a rise in sexual dysfunction with increasing stages of endometriosis. The rate of FSD increased from 33.33% in patients with minimal endometriosis to 100% in those with severe endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a retrospective investigation found a link between profound dyspareunia and bladder discomfort [ 21 ]. Additionally, in a prospective investigation, it was shown that painful bladder syndrome and levator ani tenderness, unrelated to tenderness at other anatomic locations, were associated with more severe deep dyspareunia [ 22 ]. The role of interstitial cystitis and stress urinary incontinence on dyspareunia are shown in the next sections of this review.…”
Section: Dyspareuniamentioning
confidence: 99%
“…Unfortunately, no therapy method examined thus far has shown to ameliorate sexual dysfunction in the IC/BPS population. Although sexual dysfunction is more common in IC/BPS patients than in controls, it has been suggested that treating the condition alone may not be enough to address the multiple causes of sexual dysfunction [ 22 ].…”
Section: Interstitial Cystitis/painful Bladder Syndrome (Ic/pbs)mentioning
confidence: 99%